(untitled) (Journal of the College of Basic Education, 2022)
E-Government is the default version of the Government of the material, but in cyberspace, and means simply, the e-government include the provision of public services through advanced technology, including the Internet andusing them to do so E-government aims to make the State more relevant to the attention of citizens, and the technology for he is a tool in this Effort .E-government success requires a change in the way the government’s performance and handling with the information and the way to be considered Officials from which the functions they perform and how to deal with citizens. It also requires that partnership vital link between government and citizens and the private sector